Congenital T-cell activation impairs transitional-to-follicular B-cell maturation in humans - Hugues Allard-Chamard; Kirsty Hillier; Michelle L. Ramseier; Alice Bertocchi; Naoki Kaneko; Katherine Premo; Grace Yuen; Marshall Karpel; Vinay S. Mahajan; Christina Tsekeri; Joseph S. Hong; Jean Vencic; et al. (Blood Advances)
Abstract: Patients with cytotoxic T-lymphocyte–associated protein 4 (CTLA4) deficiency exhibit profound humoral immune dysfunction, yet the basis for the B-cell defect is not known. We observed a marked reduction in transitional-to-follicular (FO) B-cell development in patients with CTLA4 deficiency, correlating with decreased CTLA4 function in regulatory T cells, increased CD40L levels in effector CD4+ T cells, and increased mammalian target of rapamycin complex 1 (mTORC1) signaling in transitional B cells (TrBs). Treatment of TrBs with CD40L was sufficient to induce mTORC1 signaling and inhibit FO B-cell maturation in vitro. Frequent cell-to-cell contacts between CD40L+ T cells and immunoglobulin D–positive CD27– B cells were observed in patient lymph nodes. FO B-cell maturation in patients with CTLA4 deficiency was partially rescued after CTLA4 replacement therapy in vivo. We conclude that functional regulatory T cells and the containment of excessive T-cell activation may be required for human TrBs to mature and attain metabolic quiescence at the FO B-cell stage.